Новое в механической обработке металлов: [сборник] - Чуев А. В.; Грущецкий Г. Н.; Евдокимов К. Л. Константин Лаврентьевич; Матвеев П. Н. Петр Николаевич; Павлов А. Г.; Сафонов И. И.; Семенов А. А. (Новаторы Ленинграда предлагают)
Авт. указ. на обороте тит. л.